Abuela, don't forget me - Ogle, Rex (Norton Young Readers, 2022)
A collection of poems celebrating and remembering the author's beloved abuela, grandmother, who, while he was growing up, was the only source of happiness and comfort in his life of poverty and domestic abuse. When his grandma began to become forgetful, even forgetting him in the middle of their conversations sometimes, the author began writing his sorrow and memories in little snippets, then in the poems that became this book.